2016
DOI: 10.1177/1359105316630134
|View full text |Cite
|
Sign up to set email alerts
|

The role of familism in weight loss treatment for Mexican American women

Abstract: Mexican American women are disproportionately affected by overweight/obesity and the health complications accompanying them, but weight loss treatments are less successful in this ethnic group. High levels of familism, a value reflecting obligation to family that supersedes attention to oneself, interfere with weight loss for Mexican American women. This mixed methods study investigated overweight Mexican American women's beliefs about how familism, and Mexican American culture, might hinder weight loss succes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…Family gatherings/pressure to eat and family food preferences for unhealthy and/or traditional foods were identified as themes in focus groups with Mexican/Mexican-American women when discussing the role of familism and weight loss treatment outcomes. 46 Regular family meals have been significantly associated with family dietary quality. 47 Future research may consider investigating the role of familism in frequency of family meals and type of foods (i.e., traditional versus not) served at the table among Hispanic families.…”
Section: Discussionmentioning
confidence: 99%
“…Family gatherings/pressure to eat and family food preferences for unhealthy and/or traditional foods were identified as themes in focus groups with Mexican/Mexican-American women when discussing the role of familism and weight loss treatment outcomes. 46 Regular family meals have been significantly associated with family dietary quality. 47 Future research may consider investigating the role of familism in frequency of family meals and type of foods (i.e., traditional versus not) served at the table among Hispanic families.…”
Section: Discussionmentioning
confidence: 99%
“…Higher adherence has also been linked to social support, older age, higher income, and education, although support from children showed no effect [15]. Lower adherence has been linked to low age, higher weight, low socioeconomic status, past negative experiences with physical activity, depressed mood, and more children living at home [16][17][18][19].…”
Section: Introductionmentioning
confidence: 98%
“…However, there is data indicating the negative role of familism in maintaining improper behavior related to health. For example: McLaughlin et al ( 52 ) found that a high level of familism, a value that reflects commitment to the family that exceeds self-care, prevents weight loss in Mexican American women. Perhaps obesity, which is a family problem, co-occurring with a high level of familism, makes it difficult to change one's eating and activity habits.…”
Section: Discussionmentioning
confidence: 99%